2015
DOI: 10.1002/jpln.201400480
|View full text |Cite
|
Sign up to set email alerts
|

The nitrate transporter NRT1.1 is involved in iron deficiency responses in Arabidopsis

Abstract: Iron (Fe) deficiency strongly induces Fe-acquisition gene expression. The nitrate transporter NRT1.1, which functions as a dual-affinity nitrate transporter and nitrate signaling sensor, is involved in many nitrate-dependent responses. However, the regulation of plant responses to Fe deficiency by NRT1.1 has not been described. In this study, it is shown that NRT1.1 is downregulated by Fe deficiency. The functional disruption of NRT1.1 enhanced resistance to Fe deficiency stress: after 10 d Fe starvation, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
0
10
2
Order By: Relevance
“…In our hydroponic system, we showed that Fe deficiency markedly downregulated the level of NRT1.1-GFP in both the shoots and roots of plants, but did not affect the gene expression of NRT1.1 in shoots and slightly decreased that in roots (Figure 1). Critical factors resulting in the discrepancy between the results reported by Liu et al (2015) and our study may be differences between the culture systems used. Furthermore, the variable NO 3 À concentrations and pH values in the growth medium may also account for the difference, as both affect NRT1.1 expression.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…In our hydroponic system, we showed that Fe deficiency markedly downregulated the level of NRT1.1-GFP in both the shoots and roots of plants, but did not affect the gene expression of NRT1.1 in shoots and slightly decreased that in roots (Figure 1). Critical factors resulting in the discrepancy between the results reported by Liu et al (2015) and our study may be differences between the culture systems used. Furthermore, the variable NO 3 À concentrations and pH values in the growth medium may also account for the difference, as both affect NRT1.1 expression.…”
Section: Discussioncontrasting
confidence: 97%
“…Previously, Fe deficiency was found to downregulate the transcription level of NRT1.1 in the shoots and roots of plants grown in an agar system (Liu et al., 2015). In our hydroponic system, we showed that Fe deficiency markedly downregulated the level of NRT1.1‐GFP in both the shoots and roots of plants, but did not affect the gene expression of NRT1.1 in shoots and slightly decreased that in roots (Figure 1).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Further studies are needed to investigate the relevant downstream signal transduction pathways of this N-P integrator. Liu et al (2015) reported that the lack of NRT1.1 enhances plant tolerance to Fe deficiency stress; however, the expression of Fe acquisition related-genes FRO2, IRT1, and FIT was lower in the nrt1.1 mutants than in wild-type plants under Fe-deficient conditions, indicating that the FIT-dependent Fe deficiency signalling pathway was not involved in NRT1.1regulated Fe deficiency responses. Because nitrate functions as a nutrient and a signalling molecule (Krouk, 2017), it is conceivable that the reduced accumulation of internal nitrate in nrt1.1 mutants may impair the FIT-dependent Fe deficiency signalling pathway.…”
Section: P and Fe Deficiencymentioning
confidence: 97%
“…In addition to its function as NO 3 - transporter, NRT1.1 also plays important roles in vegetative and reproductive growth (Guo et al, 2001), stomatal opening (Guo et al, 2003), root architecture (Remans et al, 2006; Mounier et al, 2014), and transport of chloride and phytohormones (IAA/ABA/jasmonic acid/GAs) (Tsay et al, 1993; Guo et al, 2002; Krouk, 2016; Corratgé-Faillie and Lacombe, 2017). Moreover, it induces tolerance in plants to abiotic stresses, such as proton stress, salt stress, Cd 2+ stress, and iron deficiency (Mao et al, 2014; Liu et al, 2015; Abouelsaad et al, 2016; Fang et al, 2016). NRT1.1-mediated plant stress tolerance is closely associated with NO 3 - uptake, assimilation, and accumulation.…”
Section: Introductionmentioning
confidence: 99%